Nano C-A-S-H seed crystal and nano C-A-S-H enhanced low-content high-belite cement-slag cementing material
By incorporating nano-CASH seeds into low-dosage high-belite cement-slag cementitious materials, the problem of insufficient early strength is solved, and early strength improvement and later strength growth are achieved. This reduces clinker consumption and energy consumption, meets the needs of emergency repair projects, and has environmental advantages.
Patent Information
- Application Number
- CN202511146221.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-15
- Publication Date
- 2025-11-25
AI Technical Summary
Existing technologies are insufficient to effectively address the problem of insufficient early strength in low-dosage, high-belite cement-slag cementitious material systems. Furthermore, traditional activation methods involve high energy consumption, safety risks, and environmental burdens, and cannot meet the needs of special scenarios such as emergency repairs.
Nano-CASH seeds were prepared by chemical precipitation and incorporated into low-dosage high-belite cement-slag cementitious materials. The nano-CASH seeds served as nucleation sites, promoting early hydration reactions and improving early strength. Furthermore, the high-belite cement clinker and slag achieved synergistic effects, resulting in efficient material utilization.
It significantly improves the early strength and construction efficiency of materials, ensures continuous growth in strength in the later stages, reduces clinker usage, reduces energy consumption and CO2 emissions, meets the needs of emergency repair projects, and also has environmental value.
Smart Images

Figure CN121005536A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of building materials, and particularly relates to a nano C-A-S-H crystal seed and a nano C-A-S-H reinforced low-dosage high belite cement-slag cementitious material. BACKGROUND
[0002] With the acceleration of industrialization, as a large amount of industrial solid waste generated in the steel smelting process, the large accumulation of slag not only occupies valuable land resources, but also causes soil pollution, water pollution and a series of environmental problems. Therefore, how to efficiently utilize slag has become a key issue to be solved in the industry.
[0003] At the same time, high belite cement has shown significant advantages in reducing energy consumption and CO2 emissions due to its lower clinker sintering temperature and high content of belite (β-C2S) minerals, and has become an important direction for the green transformation of the cement industry. However, this cement has the problem of slow early strength development, which seriously restricts its application in projects such as emergency repair and prefabricated components that have strict requirements on early strength.
[0004] Existing research attempts to incorporate slag as a mixed material into high belite cement systems, hoping to reduce production costs through the resource utilization of industrial waste, while improving cement performance. When the slag dosage is increased to 75-80%, the shrinkage characteristics of slag hydration products C-A-S-H can be utilized to compensate for the micro-expansion of high belite cement hydration ettringite, and the cost of cementitious materials can be significantly reduced, but problems such as early setting retardation and severe strength deficiency will occur. In low-dosage systems, due to the inherent defect of low slag activity, the synergistic effect is not good, not only is the early strength difficult to meet the engineering requirements, but the incomplete hydration reaction also limits the growth of later strength, and the durability of hardened paste is reduced due to the loose microstructure.
[0005] To overcome the above problems, existing technologies mainly focus on mechanical activation, chemical activation and mineral composition optimization. Mechanical activation increases the activity of slag by improving its grinding fineness, but has the significant disadvantages of high energy consumption and high cost, and is prone to cause particle agglomeration, resulting in poor dispersibility and workability deterioration. Chemical activation relies on activators such as alkali hydroxides and sulfates to promote slag hydration, but the activation effect is restricted by the chemical properties of slag and cement, and more seriously, some activators pose safety risks such as steel corrosion and structural expansion damage, and increase environmental burden. And will increase the environmental burden. Mineral composition optimization adjusts the ratio of high belite cement and slag to achieve synergistic effect, but due to the difficulty in changing the inherent hydration characteristics of both, this strategy cannot fully realize the expected enhancement effect.
[0006] In the cement hydration system, calcium silicate hydrate (CSH), as the core hydration product accounting for 60-70 wt%, is the main source of cement strength. Although artificially synthesized CSH gel was once highly anticipated, its structural defects have led to poorer moisture resistance, heat resistance, and corrosion resistance in cement, which in turn limits the service life and applicable scenarios of cement.
[0007] Nano-CASH (hydrated calcium aluminosilicate), a nanomaterial with a structure highly similar to the main hydration products of slag, possesses unique small-size, surface, and quantum-size effects, giving it the potential to optimize the structure of cementitious materials, enhance interfacial bonding, and accelerate the hydration reaction process at the microscopic level. However, research on applying nano-CASH to low-dosage high-belite cement-slag cementitious material systems is currently lacking. Existing technologies cannot effectively solve the problem of insufficient early strength while reducing the amount of high-belite cement clinker and increasing the slag content, making it difficult to meet the needs of special scenarios such as emergency repair projects. Therefore, developing nano-CASH-enhanced low-dosage high-belite cement-slag cementitious materials is of significant practical importance for overcoming existing technological bottlenecks and achieving efficient resource utilization of slag. Summary of the Invention
[0008] The purpose of this invention is to provide a nano-CASH seed crystal and its preparation method, which can be applied to a low-dosage high-belite cement-slag cementitious material system. While reducing the amount of high-belite cement clinker and increasing the slag content, it can also provide early strength to meet the needs of special scenarios such as emergency repair projects.
[0009] Another objective of this invention is to provide a nano-CASH-reinforced, low-dosage, high-belite cement-slag binder.
[0010] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0011] The first aspect of this invention discloses a method for preparing nano-CASH seeds, the raw materials of which include silicon source, calcium source, aluminum source, polycarboxylic acid and alkali, and are synthesized by chemical precipitation method, wherein Al / Si (molar ratio) is 0.5, Ca / Si (molar ratio) is 1.2 to 2.0, and water-solid ratio (mass ratio) is 8 to 12:1.
[0012] In some embodiments of the present invention, the silicon source includes sodium silicate nonahydrate (Na2SiO3·9H2O), the calcium source includes calcium nitrate tetrahydrate (Ca(NO3)2·4H2O), and the aluminum source includes aluminum nitrate nonahydrate (Al(NO3)3·9H2O).
[0013] In some embodiments of the present invention, the alkali is sodium hydroxide.
[0014] In some embodiments of the present invention, the preparation method of the nano-CASH seed crystals includes the following steps: placing a silicon source, polycarboxylic acid, alkali and deionized water in a reaction vessel, adding a calcium source solution and an aluminum source solution dropwise under stirring conditions, controlling the pH value of the reaction system to be 12.5-13.5, the reaction temperature to be 35-45℃, centrifuging, washing and drying after the reaction to obtain nano-CASH seed crystals.
[0015] In some embodiments of the present invention, the reaction takes 1 to 6 hours.
[0016] The second aspect of this invention discloses nano-CASH seeds prepared by the above method.
[0017] The third aspect of this invention discloses the application of the nano-CASH seed crystals in nano-CASH-reinforced low-dosage high-belite cement-slag cementitious materials.
[0018] The fourth aspect of this invention discloses a nano-CASH reinforced low-dosage high-belite cement-slag cementitious material, comprising nano-CASH seeds and cementitious material, wherein the dosage of nano-CASH seeds is 1-3 wt% of the mass of cementitious material; the cementitious material comprises granulated blast furnace slag, high-belite cement clinker and anhydrite.
[0019] In some embodiments of the present invention, the weight composition of the cementitious material is as follows: 70-85 parts of blast furnace slag, 4-8 parts of high belite cement clinker, and 12-16 parts of anhydrite.
[0020] Preferably, the weight composition of the cementitious material is as follows: 80 parts blast furnace slag, 6 parts high belite cement clinker, and 14 parts anhydrite.
[0021] The granulated blast furnace slag is grade S95 and has the following chemical composition by mass percentage: CaO: 39.7 wt%, SiO2: 28.9 wt%, Al2O3: 14.0 wt%.
[0022] In some embodiments of the present invention, the mineral composition of the high-Belit cement clinker meets the following conditions: C2S content is 45-55wt%, C4A3 content is 27-30wt%, C5S2 content is 5-10wt%, and CaSO4 content is 8-10wt%.
[0023] In some embodiments of the present invention, the anhydrite is of Class A, Grade II or above.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] This invention is scientifically designed and ingeniously conceived. It creatively incorporates nano-CASH seeds into low-dosage high-belite cement-slag cementitious materials, which not only significantly improves the early strength and construction efficiency of the materials, but also ensures the continuous growth of strength in the later stages. At the same time, it realizes the efficient utilization of low-dosage high-belite cement and slag, and has both excellent performance and environmental value.
[0026] The nano-CASH seeds of this invention serve as nucleation sites, significantly shortening the induction period of hydration in high-belite cement clinker and promoting early hydration (manifested as an increase in Ca(OH)2 formation), thereby stimulating the secondary hydration reaction of slag. This process effectively reduces the generation of temperature cracks in engineering projects. Simultaneously, the filling effect of the nano-CASH seeds optimizes the pore structure of cement stone (significantly reducing harmful pores >50nm), improving the density, strength, and durability of the system.
[0027] The components of this invention's high-belite cement-slag cementitious material also possess synergistic advantages: excellent performance is achieved through the synergistic effect of rapid hydration of high-belite cement clinker / gypsum (providing early strength and expansion) and slag pozzolanic reaction (contributing to later performance and durability), without the need for alkali activators. Its high slag content (75-80%) significantly reduces clinker usage, thereby reducing the risk of expansion cracking, while also saving costs and reducing carbon dioxide emissions.
[0028] The nano-CASH seeds of this invention provide nucleation sites for CASH gels, lower the nucleation barrier, and promote the formation of Ca. 2+ and SiO4 2- The continuous dissolution environment significantly shortens the hydration induction period. This accelerates the formation of CASH gel within the system, causing the accelerated hydration period of slag high-belite cement to begin earlier and speeding up the conversion of ettringite (AFt) to monosulfide-type hydrated calcium sulfoaluminate (AFm). These mechanisms collectively promote the development of early strength in hardened cement paste without affecting its later strength, meeting the engineering requirements for high early strength.
[0029] The aforementioned mechanism (the effect of nano-CASH seed crystals and the synergistic effect of the system) of the nano-CASH reinforced low-dosage high-belite cement-slag cementitious material of this invention reduces the risk of temperature cracking and expansion cracking. High slag utilization and low clinker demand significantly reduce energy consumption and CO2 emissions in the production process, demonstrating outstanding environmental friendliness. Attached Figure Description
[0030] Appendix Figure 1 The Fourier transform infrared spectrum of the nano-CASH seed crystal in Example 1 of this invention is shown, where C / S represents the calcium-silicon ratio. Detailed Implementation
[0031] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. Obviously, the described embodiments are merely some embodiments of this invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0032] A method for preparing nano-CASH seed crystals, the raw materials of which include silicon source, calcium source, aluminum source, polycarboxylic acid and alkali, are synthesized by chemical precipitation method, wherein Al / Si (molar ratio) is 0.5, Ca / Si (molar ratio) is 1.2 to 2.0, and water-solid ratio (mass ratio) is 8 to 12:1.
[0033] The silicon source includes sodium silicate nonahydrate (Na2SiO3·9H2O), the calcium source includes calcium nitrate tetrahydrate (Ca(NO3)2·4H2O), and the aluminum source includes aluminum nitrate nonahydrate (Al(NO3)3·9H2O).
[0034] The base is sodium hydroxide, used to adjust the pH value of the reaction system.
[0035] The preparation method of the nano-CASH seed crystals includes the following steps: placing silicon source, polycarboxylic acid, alkali and deionized water in a reaction vessel, adding calcium source solution and aluminum source solution dropwise under stirring conditions, controlling the pH value of the reaction system to be 12.5 to 13.5, the reaction temperature to be 35 to 45℃, centrifuging, washing and drying after the reaction to obtain nano-CASH seed crystals.
[0036] In some embodiments of the present invention, the reaction time is 1 to 6 hours.
[0037] A nano-CASH seed crystal was prepared using the method described above.
[0038] Application of the nano-CASH seeds in nano-CASH reinforced low-dosage high-belite cement-slag cementitious materials.
[0039] A nano-CASH reinforced low-dosage high-belite cement-slag cementitious material includes nano-CASH seeds and cementitious material, wherein the dosage of nano-CASH seeds is 1-3 wt% of the mass of cementitious material; the cementitious material includes granulated blast furnace slag, high-belite cement clinker and anhydrite.
[0040] In some embodiments of the present invention, the weight composition of the cementitious material is as follows: 70-85 parts of blast furnace slag, 4-8 parts of high belite cement clinker, and 12-16 parts of anhydrite.
[0041] Preferably, the weight composition of the cementitious material is as follows: 80 parts blast furnace slag, 6 parts high belite cement clinker, and 14 parts anhydrite.
[0042] The granulated blast furnace slag is grade S95 and has the following chemical composition by mass percentage: CaO: 39.7 wt%, SiO2: 28.9 wt%, Al2O3: 14.0 wt%.
[0043] The mineral composition of the high-Belit cement clinker meets the following conditions: C2S content is 45-55wt%, C4A3 content is 27-30wt%, C5S2 content is 5-10wt%, and CaSO4 content is 8-10wt%.
[0044] Unless otherwise specified, the aluminum-silicon ratio (Al2O3 / SiO2) and calcium-silicon ratio (CaO / SiO2) mentioned in the embodiments of the present invention refer to molar ratios.
[0045] Unless otherwise specified, all parts mentioned in the embodiments of the present invention refer to parts by weight.
[0046] Example 1
[0047] This embodiment discloses a method for preparing nano-CASH seeds according to the present invention, the specific steps of which are as follows:
[0048] According to the set aluminum-silicon ratio (Al₂O₃ / SiO₂) and calcium-silicon ratio (CaO / SiO₂), the corresponding masses of raw materials were weighed. Sodium silicate nonahydrate, NaOH, polycarboxylic acid (PCE), and deionized water were first dissolved in a three-necked flask as the reaction base solution. Then, calcium nitrate tetrahydrate and aluminum nitrate nonahydrate solutions were added dropwise to the reaction base solution using a peristaltic pump. The reaction was carried out using a constant-temperature water bath magnetic stirrer for 3 hours at 40°C. The pH of the suspension system was maintained at approximately 13 using NaOH. After the reaction, the solution was centrifuged, washed, and dried to obtain nano-CASH seed crystals.
[0049] In this embodiment, nano-CASH seeds with calcium-silicon ratios of 1.2, 1.4, 1.6, 1.8, and 2.0 when the aluminum-silicon ratio was 0.5 were prepared, and the specific feed amounts are shown in Table 1.
[0050] Table 1. Ingredients for Nano CASH Seeds
[0051]
[0052] The Fourier transform infrared spectra of the nano-CASH seeds prepared with different calcium-to-silicon ratios in this embodiment are shown in the attached figure. Figure 1 As shown. 970~830cm -1 The band is the Q band in silicon-oxygen tetrahedrons. 2The characteristic absorption peak is caused by the Si-O symmetric stretching vibration. The vibration peak gradually shifts to the right as the calcium-silicon ratio increases, indicating that the number of high-polymerization structural units generated is reduced and the degree of polymerization is decreased.
[0053] Example 2
[0054] This embodiment discloses a method for preparing nano-CASH reinforced low-dosage high-belite cement-slag cementitious materials using nano-CASH seeds. The nano-CASH seeds used in this embodiment were prepared according to the method in Example 1, with an aluminum-to-silicon ratio of 0.5 and a calcium-to-silicon ratio of 1.2.
[0055] In this embodiment, the cementitious material comprises 100 parts, including 80 parts granulated blast furnace slag, 6 parts high-belite cement clinker, and 14 parts gypsum. The amount of nano-CASH seed crystals added is 1 wt% of the cementitious material.
[0056] The preparation method is as follows: mix the cementitious material with nano-CASH seed crystals evenly.
[0057] Example 3
[0058] This embodiment discloses a method for preparing nano-CASH reinforced low-dosage high-belite cement-slag cementitious materials using nano-CASH seeds. The nano-CASH seeds used in this embodiment were prepared according to the method in Example 1, with an aluminum-to-silicon ratio of 0.5 and a calcium-to-silicon ratio of 1.2.
[0059] In this embodiment, the cementitious material comprises 100 parts, including 80 parts granulated blast furnace slag, 6 parts high-belite cement clinker, and 14 parts gypsum. The dosage of nano-CASH seed crystals is 2 wt% of the cementitious material.
[0060] The preparation method is as follows: mix the cementitious material with nano-CASH seed crystals evenly.
[0061] Example 4
[0062] This embodiment discloses a method for preparing nano-CASH reinforced low-dosage high-belite cement-slag cementitious materials using nano-CASH seeds. The nano-CASH seeds used in this embodiment were prepared according to the method in Example 1, with an aluminum-to-silicon ratio of 0.5 and a calcium-to-silicon ratio of 1.2.
[0063] In this embodiment, the cementitious material comprises 100 parts, including 80 parts granulated blast furnace slag, 6 parts high-belite cement clinker, and 14 parts gypsum. The dosage of nano-CASH seed crystals is 3 wt% of the cementitious material.
[0064] The preparation method is as follows: mix the cementitious material with nano-CASH seed crystals evenly.
[0065] Comparative Example 1
[0066] This comparative example is a cementitious material without nano-CASH seeds, that is, 100 parts of cementitious material contains 80 parts of granulated blast furnace slag, 6 parts of high-belite cement clinker, and 14 parts of gypsum.
[0067] Test case
[0068] Mortar specimens were prepared using nano-CASH reinforced low-dosage high-belite cement-slag cementitious materials from Examples 1-3, respectively. The mortar-to-cement ratio was 1:3 (mass ratio) and the water-to-cement ratio was 0.45 (mass ratio) during specimen preparation. The actual water consumption should be reduced by the mass of water in the nano-CASH seed crystals.
[0069] In Comparative Example 1, cementitious materials were used to prepare cement-mortar specimens with a cement-mortar ratio of 1:3 (mass ratio) and a water-cement ratio of 0.45 (mass ratio).
[0070] The mechanical strength of the mortar specimens was tested according to GB / T 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)"; the setting time of the cement paste was tested according to GB / T 1346-2024 "Test Method for Standard Consistency Water Requirement, Setting Time and Soundness of Cement". The test results are shown in Table 2.
[0071] Table 2 shows the basic performance test results of the mortars in each embodiment and comparative example.
[0072]
[0073] As shown in Table 2, compared with the comparative example, the mortar prepared by the nano-CASH reinforced low-dosage high-belite cement-slag cementitious material has a 6-hour flexural strength of up to 5.6 MPa (comparative example: 0 MPa) and a compressive strength of up to 18.4 MPa (comparative example: 3.2 MPa). The shortest initial setting time is only 31 min (comparative example: 64 min), and the highest 28-day compressive strength reaches 66.0 MPa. It not only significantly improves the early strength and construction efficiency of the material, but also ensures the continuous growth of strength in the later stage. At the same time, it realizes the efficient utilization of low-dosage high-belite cement and slag, and has both excellent performance and environmental value.
[0074] The nano-CASH seeds of this invention significantly improve the early (6h, 1d) mechanical properties of mortar. Regarding flexural strength, the 6h strength (3.1-5.6 MPa) of Examples 1-3 of this invention is much higher than that of the comparative example (0 MPa), and the 1d strength (5.1-6.8 MPa) is also significantly better than that of the comparative example (1.4 MPa). Regarding compressive strength, the advantages of the embodiments of this invention are even more significant: the 6h strength (7.6-18.4 MPa) of Examples 1-3 far exceeds that of the comparative example (3.2 MPa), and the 1d strength (12.7-25.1 MPa) is also much higher than that of the comparative example (7.6 MPa). This indicates that the incorporation of nano-CASH seeds effectively accelerates cement hydration and significantly improves the early load-bearing capacity of the mortar.
[0075] The setting time of the cementitious material using the nano-CASH seeds of this invention is significantly shortened, and the nano-CASH seeds of this invention have a significant accelerating effect on setting. The initial setting time (31-43 min) and final setting time (50-74 min) of Examples 1-3 are both reduced by nearly half compared to the comparative examples (initial setting 64 min, final setting 115 min). This greatly improves construction efficiency and is suitable for scenarios requiring rapid hardening or emergency repairs.
[0076] The cementitious materials using the nano-CASH seeds of this invention still exhibit advantages in long-term strength. The strength of all specimens continued to increase with age. At 28 days, in terms of flexural strength, Examples 1-3 (9.7-11.8 MPa) were still superior to the comparative example (9.1 MPa); in terms of compressive strength, Examples 1-3 (53.1-66.0 MPa) were also significantly higher than the comparative example (50.4 MPa). This indicates that in low-dosage high-belite cement and slag systems, nano-CASH seeds can activate material activity, achieving a dual improvement in both early and late-stage strength, breaking through the limitations of traditional composite cementitious materials in strength development.
[0077] This invention reduces the amount of traditional cement clinker used by efficiently utilizing low-dosage high-belite cement and slag, thereby reducing energy consumption and carbon emissions. It combines technological innovation with environmental value, possesses outstanding substantive features and significant progress, and has important patent protection significance and broad market application prospects.
[0078] In summary, the nano-CASH seed-reinforced low-dosage high-belite cement-slag binder of this invention is a novel cement-based material characterized by early strength, high strength, high durability, and low permeability. It fully leverages the "seed effect," "filling effect," and high activity of nanomaterials, as well as the advantages of high-belite cement, such as low heat of hydration and environmental friendliness (low calcination temperature and low CO2 emissions). This material has enormous application potential in demanding engineering fields (such as rapid construction, ultra-long life design, and service in harsh environments), representing an important direction for the low-carbon and high-performance development of cement materials.
[0079] Finally, it should be noted that the above embodiments are merely preferred embodiments of the present invention used to illustrate the technical solutions of the present invention, and are not intended to limit the invention, nor are they intended to limit the patent scope of the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention. That is to say, any changes or refinements made to the main design concept and spirit of the present invention that are not of substantial significance, but whose technical problems are still consistent with the present invention, should be included within the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention to other related technical fields are similarly included within the patent protection scope of the present invention.
Claims
1. A method for preparing nano-CASH seeds, characterized in that, The raw materials include silicon source, calcium source, aluminum source, polycarboxylic acid and alkali, and are synthesized by chemical precipitation method. The Al / Si molar ratio is 0.5, the Ca / Si molar ratio is 1.2 to 2.0, and the water-solid mass ratio is 8 to 12:
1.
2. The method for preparing nano-CASH seeds according to claim 1, characterized in that, The silicon source includes sodium silicate nonahydrate Na2SiO3·9H2O, the calcium source includes calcium nitrate tetrahydrate Ca(NO3)2·4H2O, and the aluminum source includes aluminum nitrate nonahydrate Al(NO3)3·9H2O; the alkali is sodium hydroxide.
3. The method for preparing nano-CASH seeds according to claim 1 or 2, characterized in that, The process includes the following steps: placing a silicon source, polycarboxylic acid, alkali, and deionized water in a reaction vessel, and sequentially adding a calcium source solution and an aluminum source solution under stirring conditions. The pH of the reaction system is controlled at 12.5–13.5, and the reaction temperature is controlled at 35–45°C. After the reaction, the solid and liquid are separated, washed, and dried to obtain nano-CASH seed crystals. Preferably, the reaction time is 1–6 hours.
4. A nano-CASH seed crystal, characterized in that, It is prepared by the method described in any one of claims 1-3.
5. The application of the nano-CASH seeds according to claim 4 in the preparation of nano-CASH-reinforced low-dosage high-belite cement-slag cementitious materials.
6. A nano-CASH reinforced low-dosage high-belite cement-slag binder, characterized in that, It includes nano-CASH seeds and cementitious materials, with the amount of nano-CASH seeds being 1-3 wt% of the mass of the cementitious materials; the cementitious materials include granulated blast furnace slag, high belite cement clinker, and anhydrite.
7. The nano-CASH reinforced low-dosage high-belite cement-slag binder according to claim 6, characterized in that, The weight composition of the cementitious material is as follows: 70-85 parts blast furnace slag, 4-8 parts high belite cement clinker, and 12-16 parts anhydrite.
8. The nano-CASH reinforced low-dosage high-belite cement-slag binder according to claim 7, characterized in that, The weight composition of the cementitious material is as follows: 80 parts blast furnace slag, 6 parts high belite cement clinker, and 14 parts anhydrite.
9. The nano-CASH reinforced low-dosage high-belite cement-slag binder according to claim 7, characterized in that, The granulated blast furnace slag is grade S95.
10. The nano-CASH reinforced low-dosage high-belite cement-slag binder according to claim 7, characterized in that, The mineral composition of the high-Belit cement clinker meets the following conditions: C2S content is 45-55wt%, C4A3 content is 27-30wt%, C5S2 content is 5-10wt%, and CaSO4 content is 8-10wt%.